Praktik Mokitulung dan Mogogutat dalam Adat Bolaang Mongondow : Analisis Hukum Ekonomi Syariah di Kelurahan Motoboi Kecil, Kotamobagu - Hidayatullah A.K Husein, Mohamad; Herawaty Suleman, Nenden; Suleman, Moh Rafiq; Fauzia Talibo, Najmi (JISH: Jurnal Ilmu Syariah dan Hukum, 2026)
The mokitulung and mogogutat traditions are among the important elements of the Bolaang Mongondow customary practices that remain strongly preserved in Motoboi Kecil Village. These traditions are not merely forms of communal cooperation but also function as socio-economic mechanisms that help ease the financial burden of families during wedding and funeral ceremonies. From the perspective of Sharia Economic Law, these practices are particularly interesting to examine because they embody elements of ta’awun (mutual assistance). However, the reciprocal aspect found in mogogutat also requires further analysis to determine whether it constitutes tabarru’, hibah muqayyadah, or potentially involves prohibited elements such as riba or social coercion